2013
DOI: 10.1089/cyber.2012.0695
|View full text |Cite
|
Sign up to set email alerts
|

Superman vs. BAD Man? The Effects of Empathy and Game Character in Violent Video Games

Abstract: Recent findings indicate that events in video games, as well as players' perceptions of game characters, moderate well-established video game effects. This includes the level of identification with game characters, and players' interpretation of whether or not the actions of the characters are conceived as moral. In the present study, it was tested whether manipulating empathy for well-known game characters influences video game effects in a violent beat-'em-up game. As was expected, playing the comic hero Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 27 publications
4
38
1
Order By: Relevance
“…This research investigated the effects of the moral attributes of game characters and empathy levels on player aggression. Results showed that the moral feature itself can influence player aggression: more aggressive behaviors were emerging among players in justified roles, which was contrary to our first hypothesis and inconsistent with previous findings of how game characters affect individuals ( Meier et al, 2004 ; Peña et al, 2009 ; Happ et al, 2013 ). Previous studies have indicated that behaving badly in a game increases aggression and reduces helping behavior and group cohesion.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This research investigated the effects of the moral attributes of game characters and empathy levels on player aggression. Results showed that the moral feature itself can influence player aggression: more aggressive behaviors were emerging among players in justified roles, which was contrary to our first hypothesis and inconsistent with previous findings of how game characters affect individuals ( Meier et al, 2004 ; Peña et al, 2009 ; Happ et al, 2013 ). Previous studies have indicated that behaving badly in a game increases aggression and reduces helping behavior and group cohesion.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that, when a player acted as a “good” game character in a violent video game (such as Righteous Army or Counter-Strike), the moral panic and negative emotional experience generated by playing games was less ( Hartmann and Vorderer, 2009 ; Hartmann et al, 2010 ; Weaver and Lewis, 2012 ; Shi et al, 2013 ). Research also showed that empathy lowered aggression in the justified-role condition, but enhanced aggression in the unjustified-role condition ( Happ et al, 2013 ). Additionally, players in the unjustified-role condition had more worries, pains, and other negative emotional experiences ( Happ et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially theorized for other forms of media, Cohen (2006) proposed that identification with media characters leads to a number of educational outcomes, including greater attention to and retention of messages associated with those characters. More than other media, games are particularly wellsuited to promoting identification because they allow a player to direct the actions, choose the attributes, pursue the goals, and experience the feelings of a character who represents the player in the text (Happ, Melzer, & Steffgen, 2013;Klimmt, Hefner, & Vorderer, 2009). A study of students' identification with characters in violent video games found that identification with violent characters positively predicted aggressive affect and cognition, but identification did not mediate between level of interactivity of the medium (game versus movie) and aggression or arousal.…”
Section: Presence Flow and Identification And Learning From Gamesmentioning
confidence: 99%
“…These results proved that preference of an evil moral identity in a game could affect one's in-game immoral behaviors, such as verbal hostility and anti-user behaviors, which could impede fair competition and gaming pleasure. They also implied that the moral preferences of the narrative or playing style in the system might cause malicious and rude tendencies (Happ et al 2013;Hollingdale & Greitemeyer, 2013).…”
Section: Discussionmentioning
confidence: 99%